«Il lavoro è ovunque»: forme del racconto e forme del potere nella narrativa di Giorgio Falco (Ticontre. Teoria Testo Traduzione, 2020)
«Work is everywhere», Giorgio Falco said: today, the whole life of a man is interpreted according to criteria of the productive sphere, confirming the cogency of a «capitalist realism» as the only experiential dimension. For this reason Falco places the subject-worker at the centre of his narrative, because the horizon of resistance to the prevarications of the discourse of capital has shifted within psychology. Falco first outlines a subject multiplied in the many voices that animate the sketches of Pausa caffè (2004); then, in the stories of L'ubicazione del bene (2009), he gives this subject a sociological characterization, showing the time of domestic life of the petite-bourgeoisie. Finally, in Ipotesi di una sconfitta (2017), that disjointed subject is condensed into a single life, that of the author, who transforms his story into the allegory of contemporary work experience.Using formal analysis tools (Simonetti, Tirinanzi de Medici) and the most recent theories of the present (Sennett, Fisher), we show how the choice of the narrative medium (micro-story, short story, novel) influences the representative potential of the “narration of work”. From a mimetic narration respecting the codes of the neo-capitalist discourse (fragmentarity and speed), Falco arrives at the centripetal tension of the novel which, through a stratified narration, reflects on causes and effects that are increasingly impalpable in the speed of contemporary processes. If mimesis allows irony on the common complicity with the Capital, the first-person narrative lets rise to a reflection that is also a strategy of resistance.
Keywords: lavoro, romanzo, racconto, short story, microracconto, capitalismo, fotografia, politica, immaginario, romanzo d’artista